Regional Peculiarities in Modernization Processes within the Territories of Central Siberia - Kistova, Anastasia V.; Zamaraeva, Julia S.; Pimenova, Natalia N.; Reznikova, Ksenia V.; Koptseva, Natalia P.; Seredkina, Natalia N. (International Review of Management and Marketing, 2016)
Market processes in post-socialist societies are directly connected to the values, which are specific for most of the social subjects. Dynamics of values enables insight on the probable speed of modernization in the territory where these subjects locate. It is evident that the sluggish process of modernization and the absence of required innovation activity are the key-factors of economic and socio-cultural development of the relevant territory. The paper displays research results on the meaning of the term “value” existing among such social groups as pupils and students. The true information on priority of social meaning of the term “value” in study groups were obtained, as well as the core values characteristic for these groups were revealed. The responses, expressing peripheral social meanings, were separated as a singular group. Keywords: association experiment, modernization processes, social values, Central Siberia JEL Classifications: I2, R1, Z1